Optimization of Dynamic Business Models in Increasing the Added Value of Fish Meal Products to Strengthen Nutritious Food for Coastal Communities in Sinjai Regency - Syarifuddin Mabe Parenreng; Suleha .; Muhammad Dalvi Mustafa; Mutawakkil Samjas; Ilal Khairin Al Hafid (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
This community service activity aims to empower the community of Panaikang Village, East Sinjai District, South Sulawesi, through the downstreaming of fishery products to produce value-added local products. The program, implemented by the PMM-BIMA Sinjai Team, adopts a participatory approach, involving Poklahsar and BUMDes Barugae, with a series of activities including socialization, training, and intensive mentoring. The Dynamic Business Model (BMD) is used to help MSMEs or cooperatives adapt to market changes, improve business strategies, and optimize operations through continuous adjustments based on existing challenges and innovations. The evaluation results show a significant increase in community knowledge and skills related to the application of BMD and fish product processing. The highest increase in BMD was in the action indicator, which rose by 77.57 (from 74.43 in the pre-test to 152 in the post-test), followed by mindset, which rose by 77 (from 75.33 in the pre-test to 152.33 in the post-test), then thinking at 76.66 (from 76.67 on the pre-test to 153.33 on the post-test), and finally problem at 73.75 (from 76.25 on the pre-test to 150 on the post-test). Meanwhile, the community has become skilled in operating the machines used to produce fish flour and fish noodles. This program contributes to strengthening local economic capacity, creating new business opportunities, and diversifying food and nutritional security. The sustainability of this program has the potential to provide a lasting impact.